Popular Journalism, Religious Morality, and the Canadian Imaginary: Queers and Immigrants as Threats to the Public Sphere - Mosurinjohn, Sharday (Journal of religion and popular culture, 2014)
In Canada, opposition toward GLBQ identities and practices has been almost entirely religious in nature. On the other hand, antipathy toward "undesirable" immigrant profiles—ironically, often those perceived as homophobic and misogynistic—has been articulated through arguments about the supposed incompatibility of their religious values (usually Islamic) with "Canadian" mores. This paper analyzes a variety of national news media to demonstrate how the transgressive figures of the immigrant and the queer are composed in a powerful and particular way through journalistic attitudes toward and understandings of religion. In particular, I examine a discursive framework emergent in reporting on two recent tragedies—one, the 2011 suicide of the gay Ottawa teenager Jamie Hubley, and the other, the 2009 Shafia family "honour killings." I argue that this reporting disingenuously evokes a commitment to tolerance without occasioning a substantial interrogation of what is really being tolerated and why.